GAMBARAN PENGETAHUAN TENTANG PERNIKAHAN DINI PADA SISWI SMA DI KABUPATEN OKI TAHUN 2016 - Tri Paneliawati Tri Paneliawati (STIKes Budi Mulia Sriwijaya, 2016)
Abstrak Early marriage means a grand instituisi to bind two people of the opposite sex who was a teenager in the family ties. There are several factors causing early marriage, which is a factor of personal and family factors. From personal factors teenager is because they want to avoid sin (sex), and some are due to an